Comparative histological and immunohistochemical studies of rainbow trout under ice slurry and electric stunning methods - Roberto González-Garoz; Blanca Chinchilla; Rubén Bermejo-Poza; Javier M. De Pablo-Moreno; Diego Paul Bonel-Ayuso; Elisabeth González de Chávarri; Antonio Rodríguez-Bertos; Jesús de la Fuente; Almudena Cabezas; María Teresa Díaz (Aquaculture, 2026)

Ecotoxicological assessment of UV-C/Oxidant processes for advanced treatment of aquaculture effluents - Pablo Santiago-Espiñeira; Margarita Estreya Zvezdanova; Stefanos Giannakis; David Hernández-Moreno; María Luisa Fernández-Cruz; María del Mar de la Fuente; Jorge Rodríguez-Chueca; Patricia García-Muñoz (Water Research, 2026)

Soot propensity of Eucalyptus globulus laminar flames at different coflow indices - Pablo E. Pinto; Ignacio Verdugo; Mijail Littin; Gonzalo Severino; Juan J. Cruz; Felipe Escudero; Rodrigo Demarco; Andrés Fuentes (Fuel, 2026)

Poly(3-hydroxybutyrate) production from swine wastewater and waste vegetable oil by Cupriavidus necator in nonsterile bioreactors - Benjamin Cordero-Jorquera; Izabook Gutierrez-Urrutia; Silvana Guerra-Arredondo; Matias Orellana-Saez; Ismael Fuentes; Pablo Jofre-Dupre; Raquel Lebrero; Virginia Rivero-Buceta; Andrea Carvajal; Ignacio Poblete-Castro (Bioresource Technology, 2026)

A standardized osteometric method for identifying Iberian raptors from skeletal remains - Andrea Miguel-Batuecas; Juan A. De Pablo-Moreno; Manuel Fuertes-Recuero; Ariana Fuentes-Díaz; Fernando González; Laura Suárez; Victoriano García-Matarranz; Luis Revuelta (Research in Veterinary Science, 2026)

Phragmites australis and Scirpus holoschoenus for metal(loid)s polluted groundwater remediation: a wetland mesocosm study with different exposure regimes - Aqib Hassan Ali Khan; Alberto Soto-Cañas; Carlos Rad; Andrea Martin-Pablo; Blanca Velasco-Arroyo; Dalia de la Fuente-Vivas; Laura Gómez-Cuadrado; Gonzalo Salazar-Mardones; Herwig De Wilde; Alfredo Pérez-de-Mora; Rocío Barros (Journal of Hazardous Materials, 2026)

Beyond the landscape: Social-behavioral factors as the true coexistence parameters in the Chilean carnivore–livestock conflict - Silvio J. Crespin; Diego Aravena-Coronado; Rodrigo Fuentes-Robles; Alberto J. Alaniz; Pablo M. Vergara; Dario Moreira-Arce (Ambio, 2026)

Key factors of the deranged antiviral response in elderly patients with COVID-19: a machine-learning analysis - Tamara Postigo-Casado; Alicia Ortega; Alejandro Álvaro-Meca; Daniel Vélez-Serrano; Nadia García-Mateo; Ana P. Tedim; Raquel Almansa; Jose María Eiros; David de Gonzalo-Calvo; Anna Moncusí-Moix; Clara Gort-Paniello; Manel Perez-Pons; et al. (GeroScience, 2026)
Age is a well-known risk factor to develop severe viral respiratory infections, including severe COVID-19. This study aimed to identify the biological alterations linked to severe disease in elderly patients with COVID-19. For this purpose, we employed a derivation cohort with 450 SARS-CoV-2 infected and unvaccinated patients admitted to hospital wards and a validation cohort with 244 SARS-CoV-2 infected and unvaccinated patients admitted to hospital Intensive Care Unit (ICU). Twenty-one biomarkers were measured in plasma samples from patients upon admission, including SARS-CoV-2 RNA, IgG antibodies, and protein biomarkers. Patient cohorts were divided into two groups based on age: adult (≤ 70 years old) and elderly (> 70 years old) patients. In the derivation cohort, 90-day mortality rate observed in the adult group was 6.0% whereas in the elderly group it rises to 31.6%, same trend was noticed regarding the validation cohort, with 11.2% versus 40.3% 90-day mortality rates for adult and elderly groups, respectively. The machine-learning framework XGBoost-SHAP, fed with the plasma biomarkers information, was used to profile an age-related host response to SARS-CoV-2 infection. Based on SHAP plot, elderly patients had a strong thrombo-inflammatory response profile (significantly elevated plasma levels of: lipocalin-2, endothelin-1, D-dimer) combined with deficient adaptive and cytotoxic antiviral responses. Model performance evaluated with the validation cohort confirmed the robustness and generalizability of the model developed (AUC = 0.710). In conclusion, the machine learning approach we built allowed us to identify the presence of a deranged host response in elderly patients with COVID-19 linked to poor viral control and increased mortality. Graphical Abstract

Regional vs local LSTM models for short-term streamflow forecasting under operational constraints - Jorge Saavedra-Garrido; Jorge Arevalo; Luis De La Fuente; Aldo Tapia; Christopher Paredes-Arroyo; Ana Maria Cordova; Daira Velandia; Pablo Álvarez; Héctor Reyes-Serrano; Rodrigo Salas (Environmental Modelling & Software, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

An open, reproducible benchmark of daily CO2 forecasting models with applications to GHG monitoring - Pablo Catret-Ruber; David Garcia-Rodriguez; Domingo J. Iglesias Fuente; Ernesto López-Baeza; J. Javier Samper-Zapater; Juan José Martínez Durá (Environmental Modelling & Software, 2026)

Repeat Expansions in a Chilean Cohort with Adult-Onset Cerebellar Ataxia - M. Leonor Bustamante; Marcelo Miranda; David Pellerin; Mariana Barreto; Claudia Silva; Ana C. Miranda; Benjamín Pizarro-Galleguillos; Octavio Azaldegui; Valentina Besa; Francisca Canals; María Eugenia Contreras; Marie-Josée Dicaire; et al. (The Cerebellum, 2025)

Microbial inoculum selection for product composition tuning in methane-arrested anaerobic leach bed reactors - Andrea Carvajal; Juan de la Fuente; Pablo Santibañez; Pablo Jofré-Dupré; Daniel Navia; Andrés Donoso-Bravo; Ignacio Poblete-Castro; Antonio Serrano (Journal of Environmental Chemical Engineering, 2025)

Preventive conservation of amber: some preliminary investigations. Pyrite Decay in Amber: Deterioration of Collections and Conservation Guidelines - Rafael Pablo Lozano; Rafael López Del Valle; Eleuterio Baeza; Graciela Delvene; Eduardo Barrón; Enrique Peñalver; Ana Rodrigo; Ricardo Pérez-de la Fuente (Geoheritage, 2025)
Fossilised plant resin (amber) collections represent invaluable sources of information about the past. However, amber is particularly sensitive to exposure to light and oxygen, as well as changing temperature and humidity, rendering its preservation a major challenge. Here we reveal significant degradation of raw and carved amber specimens from part of the Early Cretaceous amber collection of Rábago-El Soplao (Cantabria, Spain), extracted more than a decade ago. These amber specimens, which originated from resin namely formed under subaerial conditions and so generally lack bioinclusions, are of remarkable importance from the palaeoecological, taphonomic, and physicochemical standpoint. Deterioration in amber pieces is due to pyrite decay resulting from the oxidation and hydration of iron sulphides in sedimentary rock remains intimately associated with the amber. We structurally, chemically and morphologically characterise hydrated-sulphate efflorescences found adhered on or included in amber as thin veins or nodules. Clays from sedimentary rock remains associated with the amber play a dual role: they react with acid derived from the dissolution of previous pyrite or sulphates to provide Al, Si, and K that are incorporated into the new sulphates, and they reinforce the alteration of pyrite by hygroscopically capturing water. We also provide guidelines for preventing and remedying pyrite disease in amber specimens, including treatment for new specimens entering collections, optimal physicochemical conditions for storage, and conservation for mildly-altered specimens. Our results urge putting measures in place to guarantee the integrity of the raw and polished amber pieces from the Rábago-El Soplao collection, and are more broadly relevant for the conservation of amber in palaeontological, mineralogical, gemological, and archaeological contexts.

CEB-01 membrane loaded with SN-38 for local post-resection control and metastasis reduction in preclinical pancreatic cancer models - Anna Huguet Ninou; Pablo Caruana; Luc Marti; Jose Tornero; Ester Lopera de Llanos; Francesc Cano Casas; Noa De la Fuente; Fátima Aguilar-del Castillo; Carlos García-Sanchez; Carmen Cepeda-Franco; Javier Padillo-Ruíz; María Virtudes Céspedes (Drug Delivery and Translational Research, 2025)
Pancreatic cancer (PC) is an aggressive malignancy with extremely poor prognosis, in which resection surgery remains the only therapeutic option with curative intent. Patients often present with locoregional metastases in lymph nodes, peritoneum and liver at diagnosis (~ 50–60% of patients), precluding the possibility of surgical resection. In addition, majority of patients develop tumor recurrence after surgery, which can be local or metastatic, in both cases negatively affecting survival outcomes. Irinotecan has proven effective as an adjuvant setting after surgery and currently used in chemotherapeutic combination regimes for the management of PC. The extreme low solubility of irinotecan’s active metabolite, 7-ethyl-10-hydroxycamptothecin (SN-38), along with its instability at physiological pH, creates significant challenges for SN-38 systemic administration as a free drug, despite its much greater potency compared to irinotecan. CEB-01 is a novel formulation of SN-38 in the form of a biodegradable nanofiber Poly (Lactic-co-Glycolic Acid) (PLGA) membrane. Implanted in the PC surgical bed, CEB-01 releases SN-38 in a prolonged manner for tumor growth control. Using in vivo pancreatic models, CEB-01 shows statistically significant reduction of postoperative tumor growth at local concentrations of SN-38 between 25 and 50 µg/cm 2 , both as monotherapy and in combination with chemotherapy (5-FU 30 mg/kg and 90 mg/kg leucovorin), in MIA PaCa-2 and metastatic Panc-1 pancreatic xenograft models. In addition, CEB-01 shows statistically significant effect on metastatic control, by reducing the number of metastases in liver, lymph nodes, and peritoneum in treated animals. Overall, no systemic toxic effects or changes in body weight were observed, confirming that CEB-01 shows a tolerable profile after post-surgical resection in in vivo models of PC. In conclusion, CEB-01 is a feasible drug delivery strategy for the local release of SN-38 as an add-on adjuvant to current PC treatments, strategy that could potentially reduce systemic side effects compared to intravenous administration of irinotecan. Graphical abstract

Thinking big! Landscape-scale evaluation of pesticide pollution and ecological risks in a protected mediterranean wetland - Pablo Amador; Valerio Gherardi; Yasser Fuentes-Edfuf; Claudia Martínez-Megías; Andreu Rico (Environmental Pollution, 2025)

Cancer spectrum in Mexican patients with the CHEK2 p.(Leu236Pro) variant: a retrospective study - L. Leonardo Flores-Lagunes; Rosa María Alvarez-Gómez; Carolina Molina-Garay; Marco Jimenez-Olivares; Pablo Arturo Acosta-Mendez; Joaquin García-Solorio; Sebastián Prida-Riba; Karol Carillo-Sanchez; Elvia Cristina Mendoza-Caamal; Marcela Angélica De la Fuente-Hernández; Verónica Zoraya Fragoso-Ontiveros; Rodrigo Estefano Reyes Casarrubias; et al. (Familial Cancer, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Phrynops Wagler, 1830 (Testudines, Chelidae) in the Late Miocene of Palo Pintado Formation, Salta Province, Argentina, with comments on taxonomy and paleoenvironmental settings - Marcelo S. de la Fuente; Carlos A. Luna; Alfredo E. Zurita; Claudia I. Galli; Sofía I. Quiñones; Juan M. Robledo; Adriana M. Candela; Enzo M. Landa Ramírez; Pablo González Ruiz; Ricardo N. Alonso (Journal of South American Earth Sciences, 2025)

Optimizing supply chains of citrus products with analysis across several design configurations - María Emilia Iñigo Martínez; Rodrigo Fuentes; Aldo Ploper; Dora Paz; Alejandro Pablo Arena (Environment Systems and Decisions, 2025)

Corrigendum to “Aerosol retrievals derived from a low-cost Calitoo sun-photometer taken on board a research vessel” [Atmos. Environ. 341 (2024) 120888] - Rosa D. García; África Barreto; Celia Rey; Eugenio Fraile-Nuez; Alba González-Vega; Sergio F. León-Luis; Antonio Alcantara; A. Fernando Almansa; Carmen Guirado-Fuentes; Pablo González-Sicilia; Victoria E. Cachorro; Frederic Bouchar (Atmospheric Environment, 2025)

CO hydrogenation in a microreactor under non-differential regime: Kinetics, and impact of reactor design and operational variables - Ismael Fuentes-Pereira; Robert E. Hayes; Adriana Blanco; Ignacio Poblete-Castro; Pablo Donoso-García; Francisco Gracia (Fuel, 2025)

Development of a new micellar formulation of carvedilol and curcumin to enhance blood pressure reduction in a spontaneously hypertensive rat model - Yanina Alejandra Santander Plantamura; Miguel Allo; Jennifer Riedel; Pedro Fuentes; Ana Sol Riesco; Ezequiel Bernabeu; Mariana Garcés; Pablo Evelson; Susana Gorzalczany; Andrea Carranza; Christian Höcht; Diego Chiappetta (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Integration of Gill and Intestinal Osmoregulatory Functions to Assess the Smoltification Window in Atlantic Salmon - Jonás I. Silva-Marrero; Floriana Lai; Sigurd O. Handeland; Cindy Pedrosa; Virginie Gelebart; Pablo Balseiro; Juan Fuentes; Ivar Rønnestad; Ana S. Gomes (Fishes, 2025)
The transfer time of Atlantic salmon smolts from freshwater to seawater remains a challenge in aquaculture, with the “smolt window” referring to the optimal timeframe for seawater readiness. Our study monitored Atlantic salmon osmoregulatory adaptations during smoltification under continuous light (LL) and winter signal regime (6 weeks LD 12:12) followed by 6 or 8 weeks of constant light. Fish were subsequently reared in seawater for 8 weeks and subjected to a stress event of cyclic hypoxia at the conclusion of the trial. Significant differences in growth trajectories were observed between the LL and LD groups, with fish receiving the winter signal showing compensatory growth after seawater transfer. Gill Na+/K+-ATPase (NKA) activity, plasma ions, glucose, and cortisol levels confirmed the importance of the winter signal for seawater adaptation. Molecular markers, including nka isoforms, Na+-K+-2Cl− cotransporter (nkcc), cystic fibrosis transmembrane conductance regulator (cftr), and Na+/HCO3− cotransporter (nbc), showed distinct temporal expression patterns, particularly in gills and midgut. Notably, the LD group with delayed seawater transfer exhibited enhanced growth and improved hypo-osmoregulatory capacity. These findings underscore the advantages of a winter signal in smoltification and suggest that delaying seawater transfer for up to 8 weeks could be beneficial.

Comprehensive air quality assessment including non-targeted approaches in primary schools from Spain - Esther Fuentes-Ferragud; Pablo Miralles; Antonio López; María Ibáñez; Juan Miguel Piera; Francisco Xavier Lopez-Labrador; Marisa Camaró; Laura López-Ocaña; Clara Coscollà (Chemosphere, 2025)

Serpin B12 in saliva of pigs: Development and analytical validation of an assay for its quantification and changes in sepsis and stress conditions - Eva Llamas-Amor; Silvia Martínez Subiela; Guillermo Ramis; Pablo Fuentes; Elena Goyena; Antonio Gonzalez-Bulnes; Edgar García Manzanilla; José Joaquín Cerón; Alberto Muñoz-Prieto; María José López-Martínez (Research in Veterinary Science, 2025)

Beyond the combustion motor: A MCDM-based approach to analyse the alternative fuel vehicle decision from the customers' point of view - David Boix-Cots; Alessio Ishizaka; Albert de la Fuente; Pablo Pujadas (Journal of Cleaner Production, 2025)

Aerosol retrievals derived from a low-cost Calitoo sun-photometer taken on board a research vessel - Rosa D. García; África Barreto; Celia Rey; Eugenio Fraile-Nuez; Alba González-Vega; Sergio F. León-Luis; Antonio Alcantara; A. Fernando Almansa; Carmen Guirado-Fuentes; Pablo González-Sicilia; Victoria E. Cachorro; Frederic Bouchar (Atmospheric Environment, 2025)

Integrated crop-livestock farms have higher topsoil nitrogen and carbon than crop-only farms in Chilean Mediterranean climate volcanic soils - Leah L.R. Renwick; Ayleen Celedón; Francisco Nájera; Juan-Pablo Fuentes Espoz; Daniela Celedón; Claudia Arellano; Osvaldo Salazar (Agricultural Systems, 2025)

Oxytetracycline dose reduction in salmon farming: Assessing a micro encapsulated novel formulation in an in vivo model - Lina Trincado; Jurij Wacyk; Silvana Cáceres; María Eugenia Rodriguez; Catalina Fuentes; Aldo Maddaleno; Ekaterina Pokrant; Andrés Flores; Pablo Salgado; Felipe Oyarzun-Ampuero; Fabrizzio Valdés; Carolina Valenzuela; et al. (Aquaculture, 2024)

Biotic and abiotic factors associated with genome size evolution in oaks - Xoaquín Moreira; Pablo Hervella; Beatriz Lago‐Núñez; Andrea Galmán; María de la Fuente; Felisa Covelo; Robert J. Marquis; Carla Vázquez‐González; Luis Abdala‐Roberts (Ecology, 2024)
The evolutionary processes that underlie variation in plant genome size have been much debated. Abiotic factors are thought to have played an important role, with negative and positive correlations between genome size and seasonal or stressful climatic conditions being reported in several systems. In turn, variation in genome size may influence plant traits which affect interactions with other organisms, such as herbivores. The mechanisms underlying evolutionary linkages between plant genome size and biotic and abiotic factors nonetheless remain poorly understod. To address this gap, we conducted phylogenetically controlled analyses testing for associations between genome size, climatic variables, plant traits (defenses and nutrients), and herbivory across 29 oak ( Quercus ) species. Genome size is significantly associated with both temperature and precipitation seasonality, whereby oak species growing in climates with lower and less variable temperatures but more variable rainfall had larger genomes. In addition, we found a negative association between genome size and leaf nutrient concentration (found to be the main predictor of herbivory), which in turn led to an indirect effect on herbivory. A follow‐up test suggested that the association between genome size and leaf nutrients influencing herbivory was mediated by variation in plant growth, whereby species with larger genomes have slower growth rates, which in turn are correlated with lower nutrients. Collectively, these findings reveal novel associations between plant genome size and biotic and abiotic factors that may influence life history evolution and ecological dynamics in this widespread tree genus.

Outcomes and clinical characteristics of the compassionate use of plitidepsin in COVID-19 patients with solid tumours, haematological malignancies or anti-CD20 antibody treatment - Jose Aguareles; Paula Villares Fernández; Carles Forné; Eva María Martí-Ballesteros; Virginia Pradillo Fernández; Gabriel Sotres-Fernandez; Adolfo de la Fuente-Burguera; Carolina Navarro-San Francisco; Luis Miguel Buzón-Martín; Teresa García-Delangue; Francesco Tommaso Aiello; Daniel Carnevali-Ruiz; et al. (Infectious Diseases, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Exploring nutrient-sensitive landscape configurations for rural communities in southern Mexico - Ivan P. Novotny; Walter A.H. Rossing; Pablo Tittonell; Mariela Fuentes-Ponce; Jeroen C.J. Groot (Landscape and Urban Planning, 2024)

Highly Selective Ratiometric Sensors for Pb2+ Based on Luminescent Zn(II)-Coordination Polymers with Thiophenedicarboxylate. Crystal Structures and Spectroscopic Studies - Georgina M. Otero-Fuentes; Victor Sánchez-Mendieta; Alejandro Sánchez-Ruiz; Raúl A. Morales-Luckie; Diego Martínez-Otero; Jonathan Jaramillo-García; Juan Pablo León-Gómez; Alejandro Dorazco-González (Journal of Fluorescence, 2024)
The development of luminescent coordination polymers for the selective sensing of Pb 2+ in water constitutes an active area of research that impacts analytical, environmental, and inorganic chemistry. Herein, two novel water-stable 2D Zn-coordination polymers {[Zn 2 (H 2 O) 2 (tdc) 2 (bpy)]·(H 2 O)} n 1 and [Zn(tdc)(tmb)] n 2 (tdc = thiophenedicarboxylate; bpy = 4,4’-bipyridine and tmb = 4,4'-trimethylenebipyridine) were synthesized, structurally determined by single crystal X-ray diffraction, and studied in-depth as luminescent sensors for a series of cations (Ca 2+ , Mg 2+ , Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ Cd 2+ , Hg 2+ and Pb 2+ ) in 20% aqueous ethanol. These Zn-polymers possess photostability in 20% aqueous ethanol with a strong emission at 410 upon excitation at 330 nm and quantum yields of around Φ = 0.09. Under these conditions, Pb +2 can be efficiently sensed with polymer 2 through a fluorescent ratiometric response with selectivity over common interfering metal ions such as Cu 2+ , Cd 2+ and Hg 2+ in the micromolar concentration range (detection limit = 1.78 ± 10 μM). Such selectivity/affinity of Pb 2+ over Hg 2+ for luminescent chemosensors is still rare. On the basis of spectroscopic tools ( 1 H NMR, far ATR-IR, PXRD), the X-ray crystal structure of 2 , and Scanning Electron Microscopy with Energy-Dispersive X-ray Spectroscopic analysis, the ratiometric fluorescent response is proposed via an efficient metal-ion exchange driven through interactions between thiophenedicarboxylate rings and Pb 2+ ions. The use of flexible luminescent Zn-coordination polymers as sensors for selective and direct detection of Pb 2+ in aqueous media has been unexplored until now. Graphical Abstract

Nitrogen compounds at Mexican and USA coasts on the Gulf of Mexico - Daimy Avila Rodríguez; Rodolfo Sosa Echeverría; Gilberto Fuentes García; Ana Luisa Alarcón Jiménez; Georgina Fernández Villagómez; Víctor Magaña; John Walker; Pablo Sánchez Álvarez (Atmospheric Environment, 2024)

Water column-based assays underestimate benthic predation pressure in mid-latitude systems - Sabine Rech; Joao Bosco Gusmao; Benjamín Aguila; Pamela Averill; Juan Pablo Fuentes; Martin Thiel (Marine Biology, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

R-phycoerythrin alginate/shellac beads by external gelation: Process optimization and the effects of gastrointestinal digestion for nutraceutical applications - Pablo Castro-Varela; Mónica Rubilar; Antonio Martínez-Férez; David Fuentes-Ríos; Juan Manuel López-Romero; Claudio Alarcón; Roberto Abdala-Díaz; Félix L. Figueroa (Algal Research, 2024)

Simultaneous direct determination of Glyphosate and AMPA in the ambient air and inhalation risk assessment in a Mediterranean Region (Spain) - Antonio López; Pablo Ruiz; Esther Fuentes; Vicent Yusà; Pablo Dualde; Pablo Miralles; Clara Coscollà (Atmospheric Environment, 2024)

Reproductive performance and egg and larvae quality from first generation peruvian grunt Anisotremus scapularis (Tschudi, 1846): a comparative analysis with spawns from wild broodstock - Noemi Cota Mamani; Lili Jannet Carrera Santos; Angélica Castro-Fuentes; Oneill Leon Dominguez; Leenin Flores Ramos; Anthony Ruiz Soto; Juan Pablo Lazo; Neil Duncan (Frontiers in Marine Science, 2023)
Anisotremus scapularis is a marine fish distributed along the Peruvian coast that is commercially important in local markets. IMARPE started research on this species aimed to condition breeders and control reproduction in captivity and avoid dependence on wild broodstock. Therefore, the present study characterized and compared the reproductive performance, quality of eggs and larvae between a first generation domesticated broodstock (F1B) and a wild broodstock (WB). The F1B and WB broodstocks were conditioned in recirculation systems (RAS) to spawn naturally from August 2021 to August 2022. The following parameters were recorded for each spawn, the total number of eggs, percentages of viable eggs and fertilization, and hatching, and biochemical analyses on each spawn were performed. Progeny from each spawning were assessed for survival activity index (SAI), and at 20 days’ post-hatch (DPH), the temperature tolerance index (TTI) was analyzed. WB had significantly higher ( P <0.05) egg production, egg diameter, oil globule diameter, and SAI than those of F1B. However, the percentage of viable eggs and hatching showed significantly higher values ( P <0.05) in F1B spawns. A low correlation (r<0.50) was observed between the evaluated reproductive parameters in A. scapularis broodstock; nevertheless, it was significant in some cases. No significant differences were observed in protein, lipid, carbohydrate, or ash content in eggs, but ash content in the 20 DPH larvae differed, with higher values in F1B. A principal component analysis (PCA), indicated a strong relationship between F1B broodstock eggs and fatty acids DHA, 16:0, 18:1n-9, and 18:2n-6; whereas fatty acids 18:0, 20:4n-3, 22:5n-3, and EPA had a high connection with WB eggs. At 20 DPH, F1B larvae had a strong link with 18:1n-9, DHA, and 18:2n-6; while WB larvae were found to have a high association with 16:1n-7, EPA, 22:5n-3, and ARA. Based on these results we concluded that F1B broodstock has better egg quality in terms of egg viability and hatching rate and similarity in most larval quality parameters compared to WB, making the F1 domesticated broodstock (F1B) an alternative to establish a broodstock under captive conditions and thus contributing to the aquaculture development of the species.

Non-target screening and human risk assessment for adult and child populations of semi-volatile organic compounds in residential indoor dust in Spain - Esther Fuentes-Ferragud; Pablo Miralles; Antonio López; María Ibáñez; Clara Coscollà (Chemosphere, 2023)

Dietary glutamine enhances growth performance and gut integrity of Totoaba macdonaldi juveniles fed low fishmeal diets but has limited synergetic effects in combination with a prebiotic - José Pablo Fuentes-Quesada; María Teresa Viana; José A. Mata-Sotres; Abelardo Campos; Camilo Pohlenz; Juan Pablo Lazo (Aquaculture, 2023)

Gaining knowledge about biomarkers of the immune system and inflammation in the saliva of pigs: The case of myeloperoxidase, S100A12, and ITIH4 - María Botía; Alba Ortín-Bustillo; María J. López-Martínez; Pablo Fuentes; Damián Escribano; Antonio González-Bulnes; Edgar G. Manzanilla; Silvia Martínez-Subiela; Asta Tvarijonaviciute; Marina López-Arjona; José J. Cerón; Fernando Tecles; et al. (Research in Veterinary Science, 2023)

A 2D/3D multimodal data simulation approach with applications on urban semantic segmentation, building extraction and change detection - Mario Fuentes Reyes; Yuxing Xie; Xiangtian Yuan; Pablo d’Angelo; Franz Kurz; Daniele Cerra; Jiaojiao Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Influence of particulate matter on air quality due to “Nortes” events in the Gulf of Mexico - Mauro Cortez-Huerta; Rodolfo Sosa Echeverría; Gilberto Fuentes García; Rafael Antonio Durán; Pablo Sánchez Álvarez; Víctor Magaña; Armando Retama (Atmospheric Pollution Research, 2023)

Planning for fear of crime reduction: Assessing the impact of public space regeneration on safety perceptions in deprived neighborhoods - Pablo Navarrete-Hernandez; Alejandra Luneke; Ricardo Truffello; Luis Fuentes (Landscape and Urban Planning, 2023)

Zinc levels of patients with a moderate to severe COVID-19 infection at hospital admission and after 4th days of ward hospitalization and their clinical outcome - Laura Rodelgo Jiménez; Arturo Corbatón Anchuelo; Pablo Matías Soler; Raúl Perales Muñoz; Manuel Fuentes Ferrer; Iñigo Sagastagoitia Fornie; Marina Gil Mosquera; Mercedes Martínez-Novillo González (Journal of Trace Elements in Medicine and Biology, 2023)

Evaluation of a miniaturized portable NIR spectrometer for the prediction of soil properties in Mediterranean central Chile - Osvaldo Salazar; Angelo Benvenuto; Mario Fajardo; Juan Pablo Fuentes; Francisco Nájera; Ayleen Celedón; Marco Pfeiffer; Leah L.R. Renwick; Oscar Seguel; Yasna Tapia; Manuel Casanova (Geoderma Regional, 2023)

Effect of selection for growth rate on the rabbit (Oryctolagus cuniculus) immune system and its response after experimental Staphylococcus aureus infection - Elena Moreno-Grua; Sara Pérez-Fuentes; David Viana; Laura Selva; Eugenio Martínez-Paredes; Pablo Jesús Marín-García; Juan José Pascual; Juan Manuel Corpa; Alberto Arnau-Bonachera (Veterinary Research Communications, 2023)

Identifying sustainability priorities among value chain actors in artisanal common octopus fisheries - Gillian B. Ainsworth; Pablo Pita; Cristina Pita; Katina Roumbedakis; Graham J. Pierce; Catherine Longo; Gregory Verutes; Tereza Fonseca; Daniela Castelo; Carlos Montero-Castaño; Julio Valeiras; Francisco Rocha; et al. (Reviews in Fish Biology and Fisheries, 2023)
The United Nations (UN) Decade of Ocean Science highlights a need to improve the way in which scientific results effectively inform action and policies regarding the ocean. Our research contributes to achieving this goal by identifying practical actions, barriers, stakeholder contributions and resources required to increase the sustainability of activities carried out in the context of artisanal fisheries to meet UN Sustainable Development Goals (SDG) and International Year of Artisanal Fisheries and Aquaculture (IYAFA) Global Action Plan (GAP) Pillar targets. We conducted a novel ‘social value chain analysis’ via a participatory workshop to elicit perspectives of value chain actors and fisheries stakeholders associated with two Spanish artisanal common octopus ( Octopus vulgaris ) fisheries (western Asturias—Marine Stewardship Council [MSC] certified, and Galicia—non-MSC certified) about their priorities regarding sustainable octopus production and commercialization. Our adapted Rapfish sustainability framework emphasised the importance of economic, environmental, ethical, institutional, social, and technological indicators to different actors across the value chain. We mapped participants’ shared sustainability priorities (e.g. integrated fisheries management, knowledge-based management, product traceability) to six Rapfish indicators, seven IYAFA Pillars and twelve SDGs to reveal how our results can inform ocean policy and actions. This identified how certification incentives and other cooperative approaches can facilitate environmental, economic and social sustainability (e.g. value-added products, price premiums for producers, gender inclusive organisations); support IYAFA priority outcomes (raised awareness, strengthened science-policy interface, empowered stakeholders, partnerships); and help to achieve UN SDG targets (e.g. SDG 14.b, SDG 17.17). The results can inform actors, stakeholders and policymakers about how different actors contribute to efforts to achieve the SDGs and how to manage priorities for sustainable actions within artisanal fisheries and their value chains. We recommend inclusive and equitable participatory knowledge transfer and governance platforms as part of the UN Decade of Ocean Science and beyond where participants can create theories of change towards sustainability involving the development of multi-sectoral ocean policies framed at the level of the value chain and supported by appropriate governance structures. Graphical Abstract

The prebiotic effect of agavin inclusion levels in low fishmeal diets for Totoaba macdonaldi juveniles - José Pablo Fuentes-Quesada; Benjamín Barón-Sevilla; Yanet Guerrero-Rentería; José A. Mata-Sotres; María Teresa Viana; Camilo Pohlenz; Juan Pablo Lazo (Animal Feed Science and Technology, 2023)

Highly efficient remediation of Cu (II) from water by novel poly(o-phenylenediamine)/zinc oxide nanohybrids: Kinetic, equilibrium, and thermodynamic studies - Sapana Jadoun; Juan Pablo Fuentes; Bruno F. Urbano; Jorge Yáñez (Journal of Water Process Engineering, 2023)

A review on adsorption of heavy metals from wastewater using conducting polymer-based materials - Sapana Jadoun; Juan Pablo Fuentes; Bruno F. Urbano; Jorge Yáñez (Journal of Environmental Chemical Engineering, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

A GIS-supported Multidisciplinary Database for the Management of UNESCO Global Geoparks: the Courel Mountains Geopark (Spain) - Daniel Ballesteros; Pablo Caldevilla; Ramón Vila; Xosé Carlos Barros; Laura Rodríguez-Rodríguez; Manuel García-Ávila; Elvira Sahuquillo; Miguel Llorente; José Bienvenido Diez; Mercedes Fuertes-Fuente; Susana M. Timón-Sánchez; Arturo de Lombera-Hermida; et al. (Geoheritage, 2022)
The management of a UNESCO Global Geopark (UGGp) requires a vast wealth of miscellaneous scientific knowledge that can be successfully organised using a Geographical Information System (GIS). This paper presents a pragmatic GIS database to assist in the suitable governance of the Courel Mountains UGGp (2017) in Northwest Spain. The database is structured in 66 coverages compiled from public sources and previous works or produced through traditional mapping (combining fieldwork and photointerpretation) and GIS tools. The acquired data was later homogenised and validated by a multidisciplinary team and archived in independent coverages. Forty thematic maps illustrate the broad range of cartographic information included in the GIS database. Among them, 25 basic maps provide an overview of the UGGp and 15 new maps focus on crosscutting and technical issues. All maps illustrate the huge potential of GIS to create new resources combining coverages and adapting the legend according to their purpose and audience. The database facilitates the suitable publishing of consistent outputs (e.g., brochures, books, panels, webpages, web serves), as well as the elaboration of technical data to assist the park management. The database furnishes information on the design of education actions, touristic routes, activities and Geopark facilities. The GIS database is also a supportive tool for scientific research and provides the necessary knowledge to conduct geoconservation actions based on land use, geological hazards and the occurrence of natural and cultural heritages. Altogether, the GIS database constitutes a powerful instrument for policy-making, facilitating the identification and evaluation of alternative strategy plans.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Correction to: Deep mixed ocean volume in the Labrador Sea in HighResMIP models - Torben Koenigk; Ramon Fuentes-Franco; Virna L. Meccia; Oliver Gutjahr; Laura C. Jackson; Adrian L. New; Pablo Ortega; Christopher D. Roberts; Malcolm J. Roberts; Thomas Arsouze; Doroteaciro Iovino; Marie-Pierre Moine; et al. (Climate Dynamics, 2022)

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Deep mixed ocean volume in the Labrador Sea in HighResMIP models - Torben Koenigk; Ramon Fuentes-Franco; Virna L. Meccia; Oliver Gutjahr; Laura C. Jackson; Adrian L. New; Pablo Ortega; Christopher D. Roberts; Malcolm J. Roberts; Thomas Arsouze; Doroteaciro Iovino; Marie-Pierre Moine; et al. (Climate Dynamics, 2021)
Simulations from seven global coupled climate models performed at high and standard resolution as part of the high resolution model intercomparison project (HighResMIP) are analyzed to study deep ocean mixing in the Labrador Sea and the impact of increased horizontal resolution. The representation of convection varies strongly among models. Compared to observations from ARGO-floats and the EN4 data set, most models substantially overestimate deep convection in the Labrador Sea. In four out of five models, all four using the NEMO-ocean model, increasing the ocean resolution from 1° to 1/4° leads to increased deep mixing in the Labrador Sea. Increasing the atmospheric resolution has a smaller effect than increasing the ocean resolution. Simulated convection in the Labrador Sea is mainly governed by the release of heat from the ocean to the atmosphere and by the vertical stratification of the water masses in the Labrador Sea in late autumn. Models with stronger sub-polar gyre circulation have generally higher surface salinity in the Labrador Sea and a deeper convection. While the high-resolution models show more realistic ocean stratification in the Labrador Sea than the standard resolution models, they generally overestimate the convection. The results indicate that the representation of sub-grid scale mixing processes might be imperfect in the models and contribute to the biases in deep convection. Since in more than half of the models, the Labrador Sea convection is important for the Atlantic Meridional Overturning Circulation (AMOC), this raises questions about the future behavior of the AMOC in the models.

Social Environment Ameliorates Behavioral and Immune Impairments in Tyrosine Hydroxylase Haploinsufficient Female Mice - A. Garrido; J. Cruces; N. Ceprián; C. Hernández-Sánchez; F. De Pablo; Mónica De la Fuente (Journal of Neuroimmune Pharmacology, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Inheritance and metabolomics of the resistance of two F2 populations of Phaseolus spp. to Acanthoscelides obtectus - José Cruz Jiménez-Galindo; María Tortosa; Pablo Velasco; María De La Fuente; Bernardo Ordás; Rosa Ana Malvar (Arthropod-Plant Interactions, 2020)

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Assessing water use and soil water balance of planted native tree species under strong water limitations in Northern Chile - Horacio E. Bown; Juan Pablo Fuentes; Amanda M. Martínez (New Forests, 2018)

Can conservation in protected areas and visitor preferences converge? An empirical study in Central Chile - Claudia Cerda; Juan Pablo Fuentes; Gabriel Mancilla (Biodiversity and Conservation, 2018)

The Immune System and the Role of Inflammation in Perinatal Depression - Philippe Leff-Gelman; Ismael Mancilla-Herrera; Mónica Flores-Ramos; Carlos Cruz-Fuentes; Juan Pablo Reyes-Grajeda; María del Pilar García-Cuétara; Marielle Danitza Bugnot-Pérez; David Ellioth Pulido-Ascencio (Neuroscience Bulletin, 2016)

Brain damage following prophylactic cranial irradiation in lung cancer survivors - Marta Simó; Lucía Vaquero; Pablo Ripollés; Josep Jové; Rafael Fuentes; Felipe Cardenal; Antoni Rodríguez-Fornells; Jordi Bruna (Brain Imaging and Behavior, 2016)

Integrated Structural Analysis and Life Cycle Assessment of Equivalent Trench-Pipe Systems for Sewerage - Anna Petit-Boix; Núria Roigé; Albert de la Fuente; Pablo Pujadas; Xavier Gabarrell; Joan Rieradevall; Alejandro Josa (Water Resources Management, 2016)

An effective sperm competition avoidance strategy in crabs drives genetic monogamy despite evidence of polyandry - Luis M Pardo; Marcela P. Riveros; Juan Pablo Fuentes; Noemi Rojas-Hernández; David Veliz (Behavioral Ecology and Sociobiology, 2016)

Environmental and geometric optimisation of cylindrical drinking water storage tanks - David Sanjuan-Delmás; Elena Hernando-Canovas; Pablo Pujadas; Albert de la Fuente; Xavier Gabarrell; Joan Rieradevall; Alejandro Josa (The International Journal of Life Cycle Assessment, 2015)

Differential growth rates through the seedling and sapling stages of two Nothofagus species underplanted at low-light environments in an Andean high-graded forest - Pablo J. Donoso; Daniel P. Soto; Claudio Fuentes (New Forests, 2015)

Hypothalamic-pituitary-adrenal axis function during perinatal depression - Phillipe Leff Gelman; Mónica Flores-Ramos; Margarita López-Martínez; Carlos Cruz Fuentes; Juan Pablo Reyes Grajeda (Neuroscience Bulletin, 2015)

Special features of RAD Sequencing data: implications for genotyping - John W. Davey; Timothée Cezard; Pablo Fuentes‐Utrilla; Cathlene Eland; Karim Gharbi; Mark L. Blaxter (Molecular Ecology, 2013)
Restriction site‐associated DNA Sequencing ( RAD ‐Seq) is an economical and efficient method for SNP discovery and genotyping. As with other sequencing‐by‐synthesis methods, RAD ‐Seq produces stochastic count data and requires sensitive analysis to develop or genotype markers accurately. We show that there are several sources of bias specific to RAD ‐Seq that are not explicitly addressed by current genotyping tools, namely restriction fragment bias, restriction site heterozygosity and PCR GC content bias. We explore the performance of existing analysis tools given these biases and discuss approaches to limiting or handling biases in RAD ‐Seq data. While these biases need to be taken seriously, we believe RAD loci affected by them can be excluded or processed with relative ease in most cases and that most RAD loci will be accurately genotyped by existing tools.

Human-induced changes on fine-scale genetic structure in Ulmus laevis Pallas wetland forests at its SW distribution limit - Martin Venturas; Pablo Fuentes-Utrilla; Richard Ennos; Carmen Collada; Luis Gil (Plant Ecology, 2013)

Diversity emerging: from competitive exclusion to neutral coexistence in ecosystems - Juan E. Keymer; Miguel A. Fuentes; Pablo A. Marquet (Theoretical Ecology, 2012)

Skeletal muscle signaling response to sprint exercise in men and women - Teresa Fuentes; Borja Guerra; Jesús G. Ponce-González; David Morales-Alamo; Amelia Guadalupe-Grau; Hugo Olmedillas; Lorena Rodríguez-García; David Feijoo; Pedro De Pablos-Velasco; Leandro Fernández-Pérez; Alfredo Santana; Jose A. L. Calbet (European Journal of Applied Physiology, 2012)

Effects of agriculture expansion and intensification on the vertebrate and invertebrate diversity in the Pampas of Argentina - Diego Medan; Juan Pablo Torretta; Karina Hodara; Elba B. de la Fuente; Norberto H. Montaldo (Biodiversity and Conservation, 2011)

A new species of shallow-water sea pen (Octocorallia: Pennatulacea: Kophobelemnidae) from Antarctica - Pablo J. López-González; Josep-Maria Gili; Verónica Fuentes (Polar Biology, 2009)

Mutation update of spinal muscular atrophy in Spain: molecular characterization of 745 unrelated patients and identification of four novel mutations in the SMN1 gene - Laura Alías; Sara Bernal; Pablo Fuentes-Prior; María Jesus Barceló; Eva Also; Rebeca Martínez-Hernández; Francisco J. Rodríguez-Alvarez; Yolanda Martín; Elena Aller; Elena Grau; Ana Peciña; Guillermo Antiñolo; et al. (Human Genetics, 2009)

Preparation and Analysis of an Expressed Sequence Tag Library from the Toxic Dinoflagellate Alexandrium catenella - Paulina Uribe; Daniela Fuentes; Jorge Valdés; Amir Shmaryahu; Alicia Zúñiga; David Holmes; Pablo D. T. Valenzuela (Marine Biotechnology, 2008)

The catecholaminergic RCSN-3 cell line: A model to study dopamine metabolism - Irmgard Paris; Jorge Lozano; Sergio Cardenas; Carolina Perez-Pastene; Katherine Saud; Patricio Fuentes; Pablo Caviedes; Alexies Dagnino-Ubiabre; Rita Raisman-Vozari; Takeshi Shimahara; John P. Kostrzewa; David Chi; et al. (Neurotoxicity Research, 2008)

Purification and in vitro refolding of maize chloroplast transglutaminase over-expressed in Escherichia coli - Patricia K. Carvajal-Vallejos; Alexandre Campos; Pablo Fuentes-Prior; Enrique Villalobos; André M. Almeida; Eduard Barberà; José María Torné; Mireya Santos (Biotechnology Letters, 2007)

Dietary fat, genes and insulin sensitivity - José López-Miranda; Pablo Pérez-Martínez; Carmen Marin; Francisco Fuentes; Javier Delgado; Francisco Pérez-Jiménez (Journal of Molecular Medicine, 2007)

Small-scale spatial variation in the interactions between Prunus mahaleb and fruit-eating birds - Marcelino Fuentes; José Guitián; Pablo Guitián; Teresa Bermejo; Asier Larrinaga; Pilar Amézquita; Salvatore Bongiomo (Plant Ecology, 2001)

Gene structure of the mouse leukocyte cell surface molecule Ly9 - Victoria Tovar; Miguel Angel de la Fuente; Pilar Pizcueta; Jaime Bosch; Pablo Engel (Immunogenetics, 2000)